2004
DOI: 10.2514/1.1683
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intercycle Ice Accretions on Airfoil Performance

Abstract: Results are presented of an experimental study designed to characterize and evaluate the aerodynamic performance penalties of residual and intercycle ice accretions that result from the cyclic operation of a typical aircraft deicing system. Icing wind-tunnel tests were carried out on a 36-in. chord NACA 23012 airfoil section equipped with a pneumatic deicer for several different Federal Air Regulation 25 Appendix C cloud conditions. Results from the icing tests showed that the intercycle ice accretions were mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 7 publications
5
54
1
1
Order By: Relevance
“…Changes in Mach number from 0.10 to 0.28 at Re 12:2 10 6 did have slightly more effect on the icedairfoil performance, with a small increase in drag coefficient over this range. These results are consistent with previous aerodynamic studies of iced airfoils [8,23,[28][29][30][31].…”
Section: A Full-scale Resultssupporting
confidence: 83%
“…Changes in Mach number from 0.10 to 0.28 at Re 12:2 10 6 did have slightly more effect on the icedairfoil performance, with a small increase in drag coefficient over this range. These results are consistent with previous aerodynamic studies of iced airfoils [8,23,[28][29][30][31].…”
Section: A Full-scale Resultssupporting
confidence: 83%
“…The authors also reported similar Mach number trends in maximum lift behavior in the iced airfoil configurations at Re = 6.4×10 6 . More recently, Broeren, et al 21 carried out performance measurements on a NACA 23012 airfoil with intercycle ice castings. In this case there was a slight increase in C l,max (less than 0.05) between Re = 2.0×10 6 and 3.5×10 6 , but no further increase in C l,max up to Re = 10.5×10 6 was observed for all four iced airfoil configurations.…”
Section: Iced Airfoil Resultsmentioning
confidence: 99%
“…26 The ice shapes tested by Broeren, et.al., in the NASA LTPT were all formed at a zero degree angle of attack in the BF Goodrich icing tunnel. 51 The drag results shown in Figure7 are dramatic. Although these are section drag coefficients, and there are questions regarding scale effects between the 36 inch chord model used in these tests and a full scale wing, the effects of accreting ice at a low angle of attack and then increasing that angle can be seen clearly.…”
Section: Aerodynamic Relationshipsmentioning
confidence: 83%
“…Broeren, et.al., 51 showed differences in the lift curves for a typical airfoil section, the NACA 23012, when tested at high Reynolds numbers with a variety of intercycle ice shapes and a standard, distributed roughness. Figure 7a shows the results for the intercycle shapes; Figure 7b the results for the sandpaper roughness.…”
Section: Aerodynamic Relationshipsmentioning
confidence: 99%